2015
DOI: 10.1002/ejic.201403162
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alkaline‐Earth Counterions on the Architectures, Band‐Gap Energies, and Proton Transfer of Triazole‐Based Coordination Polymers

Abstract: Increased thermal or mechanical stability of DNA duplexes is desired for many applications in nanotechnology or ‐medicine where DNA is used as a programmable building block. Modifications of pyrimidine bases are known to enhance thermal stability and have the advantage of standard base‐pairing and easy integration during chemical DNA synthesis. Through single‐molecule force spectroscopy experiments with atomic force microscopy and the molecular force assay we investigated the effect of pyrimidines harboring C‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The electronic structure calculations on these types of compounds predicted that the HOMO-LUMO gap of the organic ligand determines the band gap of these materials. [52][53][54] In this case, the band gap energy varies from 3.70 eV to 3.85 eV for compounds 1-4. The band gap 3 .70 ± 0.03 Gd-CA (2) 3 .76 ± 0.02 Tb-CA 33 .85 ± 0.01 Dy-CA (4) 3 .75 ± 0.01 energy of the Na-salt of the ligand was 3.84 eV.…”
Section: Band Gap Energymentioning
confidence: 97%
“…The electronic structure calculations on these types of compounds predicted that the HOMO-LUMO gap of the organic ligand determines the band gap of these materials. [52][53][54] In this case, the band gap energy varies from 3.70 eV to 3.85 eV for compounds 1-4. The band gap 3 .70 ± 0.03 Gd-CA (2) 3 .76 ± 0.02 Tb-CA 33 .85 ± 0.01 Dy-CA (4) 3 .75 ± 0.01 energy of the Na-salt of the ligand was 3.84 eV.…”
Section: Band Gap Energymentioning
confidence: 97%
“…Knowledge of the tautomeric preferences in organic molecules, especially in tetrazoles and triazoles, is of importance since their functionality or physicochemical activity may be tautomer sensitive [14][15][16][17]. A number of papers have been published concerning different triazole tautomers, solvent effects on the equilibria between them [18][19][20][21] as well as the proton transfer phenomena in azole-based coordination polymers [22]. However, to the best of our knowledge, UV-induced proton transfer between azole tautomers was not reported.…”
Section: Introductionmentioning
confidence: 96%
“…29,30 This cluster solid was the first demonstration of space quantization at a macroscopic scale as each Mn 12 O 12 cluster had a magnetic anisotropic energy of around 51 K. 28,29 The ability to control the optical band gap energy of a material is valuable for photocatalytic and optoelectronic applications. 7,8,[31][32][33][34][35][36] Understanding the features that control the band gap energy of a material requires systematic synthesis of a set of materials with variable linkers and/or metal motifs. Previous studies have shown that by varying the linker or the cluster motif, the optical band gap energy of MOFs and cluster solids may be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that by varying the linker or the cluster motif, the optical band gap energy of MOFs and cluster solids may be controlled. 7,[34][35][36][37][38] Generally, one does not expect magnetic materials to have a significant band gap since the majority or minority manifolds are not fully occupied. In the present case, Mn 2+ has a 3d 5 configuration in which the majority spin shell is filled, while the minority 3d shell is empty, and therefore the system could be expected to show a significant optical band gap.…”
Section: Introductionmentioning
confidence: 99%